Principais assuntos de auditoria e decisão de investimento: um estudo experimental no contexto brasileiro - Fiorin, Mariana Aparecida Favero (2023)
This research aims to analyze the impact of Key Audit Matters (PAAs) on the decision-making of non-institutional investors. With the increase in criticism regarding the informational content of Independent Audit Reports (RAIs), there is a growing effort by regulators to change auditing standards with a view to improving informational content and, consequently, helping users in decision making of investment. In this sense, in 2016 there were changes in auditing standards in Brazil, among which the Brazilian Accounting Standard – Auditing Technique 701 (NBC TA 701) stands out, which provides for the communication of PAAs in the RAIs. After changes to audit standards, Silviu and Timea (2015) suggested that the inclusion of PAAs in RAIs is based on the Theory of Inspired Confidence (TCI), evidenced by Limperg (1932), as it states that the information contained in RAIs aims to confer credibility on users when analyzing financial statements (DFs) to make investment decisions. In recent years, the number of noninstitutional investors (individuals) has grown, which suggests the need to understand how the informational content of RAIs assists in the decision-making process of these users. Given this context, an experiment was carried out, with a 2x1 research design between participants (between) manipulating (i) Absence of PAA and (ii) Presence of PAA. In both manipulations, the participant had to make his investment decision. The analysis techniques used were descriptive statistics, Wilcoxon-Mann-Whitney, Kruskal-Wallis, and marginal effects graphs, with the help of R software for data analysis. The results showed that the disclosure of PAAs did not affect the decision-making of Brazilian non-institutional investors for the scenario in which the audit opinion was unmodified (without reservation) and for the scenario in which the audit opinion was modified (with reservation). It was also observed that users tend to rarely use RAIs for investment decisions including for the scenario with modified opinion. In this sense, this study has the potential to contribute to non-institutional investors, regulators, auditors and other parties interested in this topic, as it provides empirical evidence of the relationship between the disclosure of PAAs and the investment decision-making process, as well as how it influences the expansion of information regarding the impact of audit regulatory changes.